Kryteria racjonalizacji wydatków oświatowych - Maj, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Tasks related to education which are running kindergarten, primary schools and gymnasiums belong to the most crucial own tasks of communes. Realization of this group of tasks becomes more and more difficult due to two reasons. The first reason is demographic changes (falling number of births) what has influence on falling number of pupils in schools. The second one is permanent deficit of resources that comes from educational part of general subsidy which do not cover the costs of running educational institutions. These circumstances show that the problem of the best activity schools and the financial aspects of this issue are getting important for local government. This paper is an attempt of defining criteria which can be used by local government in process of rationalization of educational expenses. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 361-372